Demographic characteristics of patients undergoing aortic valve replacement for stenosis: relation to valve morphology. Issue 2 (February 1996) - Davies, M. J.; Treasure, T.; Parker, D. J.
Abstract : OBJECTIVE: To determine the relative importance of the different causes of isolated aortic valve stenosis in a surgical series, and to relate these to patient characteristics including the rate of insertion of bypass grafts for coronary artery disease. DESIGN: Survey of the clinical and pathological data on patients undergoing aortic valve replacement for isolated stenosis. SETTING: Tertiary care cardiothoracic surgical unit. PATIENTS AND METHODS: 465 adult patients undergoing aortic valve replacement representing a consecutive series in one surgical unit. Retrospective review of patients records and classification of cause of aortic stenosis based on pathological examination of excised valve cusps. RESULTS: 63.7% patients had calcific bicuspid valves, 26.9% tricuspid calcific valves, and 5.4% rheumatic, 2.6% mixed pathology and 1.5% unicommissural valves. The ratio of males to females for bicuspid valves was 1.85:1 and for tricuspid calcific valves 0.76:1. The mean age of patients with bicuspid valves was 64.9 years compared with 73.4 years for those with tricuspid valves. Some 22.3% of patients with bicuspid valves and 44.8% of those with tricuspid valves had sufficient coronary artery disease to necessitate insertion of coronary bypass grafts. The differential rate of insertion of coronary bypass grafts was independent of age. CONCLUSIONS: Bicuspid calcified aortic valves are the predominant cause of isolated aortic valve stenosis followed by tricuspid calcified aortic valves. The sex and age distribution of bicuspid and tricuspid calcific aortic valve stenosis is different. The higher rate of insertion of vascular grafts in tricuspid calcific aortic valves may indicate that risk factors for atherosclerosis enhance cusp calcification in these patients.